Bioactive protein hydrolysates in the functional food ingredient industry: Overcoming current challenges. Issue 3 (4th May 2017) - Lafarga, Tomas; Hayes, Maria
ABSTRACT: Meat proteins and associated by-products can be used as a source of bioactive hydrolysates and peptides with potential for use as functional food ingredients. Functional foods are foods that have a potentially positive effect on health, beyond basic nutrition. Numerous bioactive peptides, including angiotensin-I-converting enzyme (ACE-I, EC 3.4.15.1) and dipeptidyl peptidase-IV (DPP-IV, EC 3.4.14.5) inhibitors, have been generated from meat by-product proteins to date. However, in order to use and commercialize bioactive hydrolysates and peptides as food ingredients, a number of significant challenges must first be overcome. This article gives an overview of the current state-of-the-art of meat-derived bioactive hydrolysate and peptide uses in the food industry. It also reviews frequent challenges faced when developing biologically active hydrolysates and peptides as food ingredients. These challenges include, but are not limited to, high production costs, negative sensory attributes in end products, taste modifications of carrier food products and compliance with, for example, the European Food Safety Authority (EFSA), the Food and Drug Administration (FDA), and other regulatory bodies in China, or Japan, as well as potential toxicity or allergenicity. We suggest strategies that may assist in overcoming these challenges, focusing on those that may be used to improve the taste attributes of the end products.